The Critical Role of Pharmacist Interventions in Antimicrobial Stewardship Programs to Combat Antimicrobial Resistance: A Comprehensive Review (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Background: Antimicrobial resistance (AMR) is a global public health crisis threatening the effective prevention and treatment of a growing range of infections. Antimicrobial Stewardship Programs (ASPs) are coordinated interventions designed to promote the optimal use of antimicrobial agents. Pharmacists, with their unique expertise in pharmacology and microbiology, are positioned to be pivotal leaders within these programs.Methods: A comprehensive literature review was conducted using databases such as PubMed, Scopus, and Cochrane Library from 2010 to 2023. Search terms included "antimicrobial stewardship," "clinical pharmacist," "pharmacist interventions," "antibiotic resistance," and "prospective audit and feedback."Findings: Pharmacist-led interventions within ASPs are highly effective across diverse healthcare settings. Key interventions include prospective audit and feedback (PAF), formulary management and pre-authorization, education, and dose optimization. These activities consistently result in improved antibiotic appropriateness, reduced antimicrobial consumption, decreased hospital length of stay, lower rates of Clostridioides difficile infection, and significant cost savings. The integration of pharmacists into multidisciplinary teams is a critical success factor.Interpretation: Pharmacists are indispensable members of the antimicrobial stewardship team. Their interventions directly contribute to combating AMR by improving patient outcomes and preserving the efficacy of existing antimicrobials. Health systems should mandate and resource the full integration of clinical pharmacists into ASPs as a standard of care.